If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -3(x + -2) = 7 + x Reorder the terms: 9 + -3(-2 + x) = 7 + x 9 + (-2 * -3 + x * -3) = 7 + x 9 + (6 + -3x) = 7 + x Combine like terms: 9 + 6 = 15 15 + -3x = 7 + x Solving 15 + -3x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 15 + -3x + -1x = 7 + x + -1x Combine like terms: -3x + -1x = -4x 15 + -4x = 7 + x + -1x Combine like terms: x + -1x = 0 15 + -4x = 7 + 0 15 + -4x = 7 Add '-15' to each side of the equation. 15 + -15 + -4x = 7 + -15 Combine like terms: 15 + -15 = 0 0 + -4x = 7 + -15 -4x = 7 + -15 Combine like terms: 7 + -15 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 14/x=7/3 | | (18+2x)/8 | | 5/-8n | | 9x^3+35x^2-4x=0 | | y-3/y-1 | | b^2/7b+7 | | 30x+8x^2=0 | | 3(4+x)=x+16 | | 14/x=7/4 | | (1.1m-0.4)sq= | | a-6/a+2 | | -34+13x=13x-34 | | 5ab+9ab=-ab | | -5/2n | | 0.4(x-6)=4.4 | | 8x+8=6x+54 | | 2d+3=5 | | 4(x+8)+x=3(x+3)+4 | | 3(4x-1)=44 | | d/4-12=-2 | | 3(4+x)=x+24 | | 14-8x=30 | | 2x+3x+8=20 | | y/3-1=4 | | -9+(-3)+7= | | 3(n-30)=45 | | -4n+25=25+3n | | 6.8x-5=5.8 | | b^2/-7b+7 | | -44+64+(-22)+51= | | x^2/2x-4 | | 6x-(37-13x)=21x-(2x+37) |